2005
DOI: 10.1136/bjsm.2003.006643
|View full text |Cite
|
Sign up to set email alerts
|

Ocular complications of boxing

Abstract: Objectives: To investigate the prevalence of ocular injuries in a large population of boxers over a period of 16 years, in particular, the most severe lesions that may be vision threatening. Methods: Clinical records of the medical archive of the Italian Boxing Federation were analysed. A total of 1032 boxers were examined from February 1982 to October 1998. A complete ophthalmological history was available for 956, who formed the study population (a total of 10 697 examinations). The following data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
3
24
1
Order By: Relevance
“…It is interesting that, during 10-year analyzed period, there was no hockey player or boxer, although these two sports represent activities with frequent eye injuries, what was also reported by other authors [13][14][15].…”
Section: Discussionsupporting
confidence: 48%
“…It is interesting that, during 10-year analyzed period, there was no hockey player or boxer, although these two sports represent activities with frequent eye injuries, what was also reported by other authors [13][14][15].…”
Section: Discussionsupporting
confidence: 48%
“…4 Most injuries to the eye region were lacerations/cuts, although conjunctival, corneal, lenticular, vitreal, ocular papilla, and retinal lesions were also reported. 3 Canadian Hospitals Injury Reporting and Prevention Program data are similar; one-third of the reported injuries affected the head, face, and neck regions, and almost half of the injuries occurred in the upper extremity (Table 2). 17 Brain injury is the most significant risk associated with boxing, and acute subdural hematoma is the most common cause of death in amateur and professional boxers.…”
Section: Types Of Injuriesmentioning
confidence: 85%
“…Participants in boxing are at risk of serious neurologic and facial injuries. [3][4][5][6][7] Despite these potential dangers, thousands of boys and girls participate in boxing in North America. In 2008, more than 18 000 youths younger than 19 years were registered with USA Boxing (Lynette Smith, USA Boxing, written communication, August 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty three articles mentioned injuries related to high risk sports as floorball (hockey), badminton, handball, basketball, golf, rugby, volleyball, water polo and soccer [2,5,6,. Considering "very high-risk" sports category, four articles had registers about boxing among which one described an isolated eyelid traumatic laceration related to karate [29][30][31][32][33][34]. Figure 1 shows the main causes of eye injuries according to sports modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, demonstrated that the use of correct eye protection could reduce or even eliminate unnecessary traumas that are easily preventable [2,5,7,[12][13][14][15]19,22,24,29]. The majority eye-trauma reports came from USA and England probably because of the great coverage of their data center and patient's information systems although those found in English articles are not specific reports.…”
Section: Discussionmentioning
confidence: 99%